Ajudaaaaa!!!!!!!!!
(x5-3ay²)²
Soluções para a tarefa
Respondido por
0
produto notavel (a-b)²=a²-2ab+b²
aplicando isso
![(x^5-3ay^2)^2=(x^5)^2-2x^5 3ay^2 + (3ay^2)^2\\\\ (x^5-3ay^2)^2=x^{5*2}-6x^5 ay^2 + 3^2a^2(y^{2}) ^2\\\\ (x^5-3ay^2)^2=x^{10}-6x^5ay^2+9a^2y^{2*2}\\\\ (x^5-3ay^2)^2=x^{10}-6x^5ay^2+9a^2y^{4} (x^5-3ay^2)^2=(x^5)^2-2x^5 3ay^2 + (3ay^2)^2\\\\ (x^5-3ay^2)^2=x^{5*2}-6x^5 ay^2 + 3^2a^2(y^{2}) ^2\\\\ (x^5-3ay^2)^2=x^{10}-6x^5ay^2+9a^2y^{2*2}\\\\ (x^5-3ay^2)^2=x^{10}-6x^5ay^2+9a^2y^{4}](https://tex.z-dn.net/?f=%28x%5E5-3ay%5E2%29%5E2%3D%28x%5E5%29%5E2-2x%5E5+3ay%5E2+%2B+%283ay%5E2%29%5E2%5C%5C%5C%5C+%28x%5E5-3ay%5E2%29%5E2%3Dx%5E%7B5%2A2%7D-6x%5E5+ay%5E2+%2B+3%5E2a%5E2%28y%5E%7B2%7D%29+%5E2%5C%5C%5C%5C+%28x%5E5-3ay%5E2%29%5E2%3Dx%5E%7B10%7D-6x%5E5ay%5E2%2B9a%5E2y%5E%7B2%2A2%7D%5C%5C%5C%5C+%28x%5E5-3ay%5E2%29%5E2%3Dx%5E%7B10%7D-6x%5E5ay%5E2%2B9a%5E2y%5E%7B4%7D)
aplicando isso
Perguntas interessantes